2022
DOI: 10.1021/accountsmr.1c00188
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Materials for Respiratory Protection: Salt-Coated Antimicrobial Fabrics for Their Application in Respiratory Devices

Abstract: Metrics & MoreArticle Recommendations * sı Supporting Information CONSPECTUS:The development of a highly effective, low-cost method for protection against direct transmission through infectious media associated with respiratory diseases has been considered to be a major challenge in the management of the pandemic outbreak. Currently, filtration in respirators and masks depends on the mesh size, raising safety concerns about direct contact with the virus-laden layers of masks and respirators during use and disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Thus, the significant level of viability loss of pathogens on the biocontaminated surface, observed from the alcohol–salt solution, can be attributed to (i) pathogen inactivation by IPA and (ii) the inactivation enhancement due to salt crystallization of the sprayed formulation during drying. According to previous reports, growing crystals during the recrystallization process were proven to effectively destroy bacteria/virus in a type- and strain-independent manner. , This explains the higher level of bacterial inactivation (i.e., ∼3-log decrease in CFU, Figure S8) by spraying bacterial suspensions in saline solutions (S5, S10, and S15). This is expected to have a maximum crystallization tendency compared to the bacteria suspended in saline solution (no viability loss: GLM analysis, P > 0.05, Figure a–c) and the bacteria-contaminated surface sprayed with saline solution (0.5–2.0-log CFUs, Figure ).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, the significant level of viability loss of pathogens on the biocontaminated surface, observed from the alcohol–salt solution, can be attributed to (i) pathogen inactivation by IPA and (ii) the inactivation enhancement due to salt crystallization of the sprayed formulation during drying. According to previous reports, growing crystals during the recrystallization process were proven to effectively destroy bacteria/virus in a type- and strain-independent manner. , This explains the higher level of bacterial inactivation (i.e., ∼3-log decrease in CFU, Figure S8) by spraying bacterial suspensions in saline solutions (S5, S10, and S15). This is expected to have a maximum crystallization tendency compared to the bacteria suspended in saline solution (no viability loss: GLM analysis, P > 0.05, Figure a–c) and the bacteria-contaminated surface sprayed with saline solution (0.5–2.0-log CFUs, Figure ).…”
Section: Resultsmentioning
confidence: 59%
“…According to previous reports, growing crystals during the recrystallization process were proven to effectively destroy bacteria/virus in a type-and strain-independent manner. 38,44 This explains the higher level of bacterial inactivation (i.e., ∼3-log decrease in CFU, Figure S8) by spraying bacterial suspensions in saline solutions (S5, S10, and S15). This is expected to have a maximum crystallization tendency compared to the bacteria suspended in saline solution (no viability loss: GLM analysis, P > 0.05, Figure 2a−c) and the bacteria-contaminated surface sprayed with saline solution (0.5−2.0-log CFUs, Figure 3).…”
Section: Antimicrobial Activities Of Ipa−nacl Solutionsmentioning
confidence: 93%
“…Respiratory bacterial and viral pathogens primarily spread through droplets and aerosols. 47 Experiments were thus performed to explore the release of CTAB upon interaction with an aqueous medium (Fig. 5, Supplementary Information Fig.…”
Section: Ctab Releasementioning
confidence: 99%
“…Salts coated onto the MAR showed good antipathogenic activity based on their recrystallization capability. [159] Quan et al developed a reusable virus inactivation technique by treating the filter membrane surface of a surgical mask with sodium chloride (NaCl) salt, which acts by dissolving upon contact with viruscontaminated aerosols and then recrystallizing through drying, thus damaging the pathogens. [156a] Carnino et al also used NaCl to treat commonly used household fabrics/materials and found filtration efficiency against the microorganisms compared to surgical masks.…”
Section: 41mentioning
confidence: 99%
“…functionalized the inner membrane (nonwoven polypropylene) of a surgical mask with three different salts (sodium chloride, NaCl; potassium sulfate, K 2 SO 4 ; and potassium chloride, KCl) to prepare a high‐performing, effective antimicrobial filtration system based on natural recrystallization. [ 156b,159 ]…”
Section: Moving Towards New Effective Materials and Technologies For ...mentioning
confidence: 99%